ANALYSIS OF ACQUISITION ON FINANCIAL PERFORMANCE IN ACQUIRING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Agung Hidayat Yusmar; Anwar Ramli; Muh. Ichwan Musa; Siti Hasbiah; Hety Budiyanti (Transpublika Publisher, 2023)
In recent years, several companies in Indonesia have engaged in acquisition activities as part of their growth and expansion strategies. The acquisition process involves one company acquiring another company, which can have various implications for the financial health and operational efficiency of both the acquiring and target companies. This study aims to analyze the comparison of the financial performance of companies listed on the Indonesia Stock Exchange before and after making acquisitions. The study uses a quantitative method with a descriptive approach, and the data used are secondary data obtained from the Indonesia Stock Exchange. In this study, the sample was obtained using purposive sampling technique, resulting in the selection of three companies that carried out acquisition activities in 2020. Data analysis in this study is divided into three parts: descriptive statistical tests, normality tests using the Kolmogorov-Smirnov test, and hypothesis testing consisting of paired sample t-tests for normally distributed data and Wilcoxon signed rank tests for data that are not normally distributed. Based on the results, it is evident that out of the eight financial ratios that have been tested, only one financial ratio experiences significant differences after making an acquisition, namely the Quick Ratio. The other seven ratios, namely Current Ratio, Total Asset Turnover, Debt to Asset Ratio, Debt to Equity Ratio, Return on Asset, Return on Equity, and Earnings Per Share, do not show significant differences. This suggests that the company has not fully optimized its performance in achieving the expected synergy through the acquisition process.